2010
DOI: 10.3748/wjg.v16.i10.1252
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of plasma adiponectin associated with increased risk of colorectal cancer

Abstract: A decreased level of adiponectin is strongly associated with an increased risk of colorectal adenoma and early cancer. These data call for further investigation, including a controlled prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 23 publications
5
72
2
4
Order By: Relevance
“…Nevertheless, one prospective study demonstrated that men with the highest concentrations had approximately 60% reduced risk for CRC compared to those with the lowest concentrations, even after adjustment for body size, WC, and physical activity (Wei et al, 2005). In contrast to prospective studies, among nine retrospective studies, only four studies have examined the association (Erarslan et al, 2009;Kumor et al, 2009;Gonullu et al, 2010;Kemik et al, 2010;Nakajima et al, 2010;Otake et al, 2010;Gialamas et al, 2011;Chen et al, 2012;Gulcelik et al, 2012). Of the four (Nakajima et al, 2010;Otake et al, 2010;Gialamas et al, 2011;Chen et al, 2012), three studies (Otake et al, 2010;Gialamas et al, 2011;Chen et al, 2012) found an inverse association between adiponectin and CRC and also suggested a protective effect of a high adiponectin level on CRC.…”
Section: Adiponectinmentioning
confidence: 99%
“…Nevertheless, one prospective study demonstrated that men with the highest concentrations had approximately 60% reduced risk for CRC compared to those with the lowest concentrations, even after adjustment for body size, WC, and physical activity (Wei et al, 2005). In contrast to prospective studies, among nine retrospective studies, only four studies have examined the association (Erarslan et al, 2009;Kumor et al, 2009;Gonullu et al, 2010;Kemik et al, 2010;Nakajima et al, 2010;Otake et al, 2010;Gialamas et al, 2011;Chen et al, 2012;Gulcelik et al, 2012). Of the four (Nakajima et al, 2010;Otake et al, 2010;Gialamas et al, 2011;Chen et al, 2012), three studies (Otake et al, 2010;Gialamas et al, 2011;Chen et al, 2012) found an inverse association between adiponectin and CRC and also suggested a protective effect of a high adiponectin level on CRC.…”
Section: Adiponectinmentioning
confidence: 99%
“…Colorectal cancer is the third most commonly diagnosed cancer in males and the second most commonly diagnosed cancer in females, with >1.2 million novel cancer cases and 608,700 mortalities estimated to occur each year. Despite considerable advances in modern therapeutic strategies, the overall survival time of patients undergoing complete resection of carcinomas is short (3). Therefore, clarification of the molecular mechanisms of colorectal carcinoma and the identification of a good biomarker to indicate the carcinogenesis and subsequent progression of the carcinoma is of considerable significance for the prevention, treatment and evaluation of prognosis of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…A decreased level of adiponectin was recognized as a strong risk factor for early CRC [6]. Two types of adiponectin receptors, AdipoR1 and AdipoR2, may be intimately related to the progression of CRC [13].…”
Section: Introductionmentioning
confidence: 99%
“…They have recently become the focus of research on the role of obesity in carcinogenesis. Several adipocytokines, namely leptin, adiponectin, visfatin and resistin, have been under investigation in a multitude of robust in vitro and epidemiological studies carried out to clarify the association between obesity and CRC [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%